Cross-cultural validation of the Child Adolescent Teasing Scale for Colombian students - Karol Johanna Briñez Ariza; Clara Virginia Caro Castillo; María Elena Echevarría-Guanilo; Marta Lenise Do Prado; Silvana Silveira Kempfer (Universidade de São Paulo, 2018)
ABSTRACT Objective: to carry out the cross-cultural validation of the instrument "Child Adolescent Teasing Scale" for the Colombian student population. Method: methodological study carried out with students aged 8 to 15, from public and private educational institutions in the municipality of Ibagué, Colombia. The form for the characterization of students and the Child Adolescent Teasing Scale were used. Results: the cross-cultural adaptation process was organized in seven steps: comparison of the Spanish version of the instrument with the original English version, back-translation, consensus version, face validity and terminology adjustment by students, face and content validity by experts, assessment committee for the final version, pilot test and reliability. Conclusion: the version adapted to the Spanish spoken in Colombia of the Child Adolescent Teasing Scale (Escala de burlas para niños y adolescentes), which assesses the frequency and distress caused by teasing, showed desirable results in terms of validity and reliability.